2016
DOI: 10.1002/adma.201604453
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Control of Graphene Flakes by Magnetic Field: Broad Device Applications of Macroscopically Aligned Graphene

Abstract: Owing to a large diamagnetism, graphene flakes can respond and be aligned to magnetic field like a ferromagnetic material. Aligned graphene flakes exhibit emergent properties approaching single-layer graphene. Anisotropic optical properties also give rise to a magnetic writing board using graphene suspension and a bar magnet as a pen. This simple alignment technique opens up enormous applications of graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 32 publications
1
66
0
Order By: Relevance
“…To fabricate more ordered laminar structure with the minimal number of nonidealities (imperfect stacking, folding, and wrinkles), 2D nanosheets should be kept horizontally aligned when depositing over each other. Besides adjusting intersheet interactions, external forces such as centrifugal, shear, compressive, and even magnetic forces may be employed in this process . 3) Transporting Mechanism : It is obvious that most studies so far endeavor to explain the mass transporting behaviors in horizontal channels including interlayer capillaries and wrinkles.…”
Section: Discussionmentioning
confidence: 99%
“…To fabricate more ordered laminar structure with the minimal number of nonidealities (imperfect stacking, folding, and wrinkles), 2D nanosheets should be kept horizontally aligned when depositing over each other. Besides adjusting intersheet interactions, external forces such as centrifugal, shear, compressive, and even magnetic forces may be employed in this process . 3) Transporting Mechanism : It is obvious that most studies so far endeavor to explain the mass transporting behaviors in horizontal channels including interlayer capillaries and wrinkles.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic fields and strain. In recent studies, responding of graphene to external factors have been reported such as an alignment of graphene sheets under the external magnetic field 73 and generating the pseudo-magnetic field by strain engineering 66,68,71 . As mentioned above, graphene properties are affected by graphene forms (suspended and supported).…”
Section: Resultsmentioning
confidence: 99%
“…41 We use a volume magnetization of 8  10 5 A/m in our simulation, so that the magnetic field is close to the experimental data of 0.3 T near the magnet. 22 Figures 2(a)-2(c) show the magnetic fields at 0.5 mm above the top surface of four interleaved magnets. The size of each magnet is 5 mm  5 mm  5 mm.…”
Section: Levitation Using Four Magnetsmentioning
confidence: 99%
“…[16][17][18] These unique properties of individual nanostructures can be exploited for large-scale macroscopic functions when they are arranged in a specific macroscopic order. 22 Diamagnetic materials, such as graphene, create a magnetic field in a direction opposite to the externally applied magnetic field, leading to a repulsive magnetic force. [23][24][25][26] Orientation control and levitation of graphene flakes are feasible with a weak magnetic field due to their high volume magnetic susceptibilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation